Pengembangan Media Pembelajaran Interaktif Berbasis Visual Basic menggunakan Metode ADDIE Materi Pencemaran Lingkungan Kelas VII SMP - Resti Yevira; Muhammad Nasir (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This study aims to create interactive learning media that are suitable and easy to learn and can be used for personal learning. Knowledge of the effectiveness of visual basic-based interactive learning media using the addie method with environmental pollution material for class VII SMP which was developed in science subjects. This type of research is development research. Product development quality data was collected by questionnaire and analyzed qualitatively and descriptively. expert test results: show the subject, instructional design, software development excellent qualifications, experiment: individual, small group, and areas of excellent qualification. Product efficacy testing was carried out using a quasi-experimental method. The result of the survey is that there are differences in student learning outcomes who are taught using interactive learning media using textbooks. The success of learning groups of students who are taught how to use interactive learning media is even more than what is taught in textbooks